Efficient Execution of Service Composition for Content Adaptation in Pervasive Computing - Yaser Fawaz; Girma Berhe; Lionel Brunie; Vasile-Marian Scuturici; David Coquil (International Journal of Digital Multimedia Broadcasting)
Multimedia content adaptation has been proved to be an effective mechanism to mitigate the problem of devices and networks heterogeneity and constraints in pervasive computing environments. Moreover, it enables to deliver data taking into consideration the user's preferences and the context of his/her environment. In this paper, we present an algorithm for service composition and protocols for executing service composition plan. Both the algorithm and the protocols are implemented in our distributed content adaptation framework (DCAF) which provides a service-based content adaptation architecture. Finally, a performance evaluation of the algorithm and the protocols is presented.